Implications of Disparities in District Court and Supreme Court Decisions in Realizing Justice: Implikasi Disparitas Putusan Pengadilan Negeri dan Mahkamah Agung dalam Mewujudkan Keadilan - Tarnama, Eins Mitchelle; Prasetyo, Boedi (Indonesian Journal of Law and Economics Review, 2026)
The general background of this study lies in the central importance of judicial consistency in upholding legal certainty within Indonesia’s criminal justice system. The specific background concerns the contrasting outcomes in the Gregorius Ronald Tannur case, where the Surabaya District Court acquitted the defendant while the Supreme Court later imposed a prison sentence, revealing potential procedural irregularities and integrity issues within the judiciary. The knowledge gap emerges from the limited scholarly examination that systematically connects judicial disparity with its legal, institutional, and socio-justice implications. This study aims to analyze the disparity between Decision No. 454/Pid.B/2024/PN.Sby and Decision No. 1466/K/Pid/2024, and to evaluate its impact on public trust, legal certainty, and judicial accountability. The results show that differences in legal interpretation, assessment of evidence, procedural deviations, and external influences contribute significantly to the disparity, with substantial consequences for the perception of justice. The novelty of this research lies in offering an integrated normative–comparative analysis that links judicial reasoning, structural weaknesses, and ethical considerations within one evaluative framework. The implications emphasize the urgent need for strengthened judicial supervision, clearer sentencing guidelines, and systemic reforms to ensure fairness, transparency, and the restoration of public confidence in Indonesia’s legal system. Highlights: Highlights how differing court decisions undermine legal certainty and consistency. Emphasizes the role of judicial integrity in maintaining public confidence. Identifies the need for stronger oversight and clearer sentencing guidelines. Keywords: Judicial Disparity, Legal Certainty, Judicial Integrity, Sentencing Inconsistency, Public Trust